Rachel Cooke: Her Brilliant Career: Ten Extraordinary Women of the Fifties - Jaine, Tom (Petits Propos Culinaires, 2013)
Rachel Cooke: Her Brilliant Career: Ten Extraordinary Women of the Fifties: Virago, 2013: 326 pp., hardback, £18.99.